Communication and Social Relations: A Qualitative Study of Families' Experience with Their Outpatient Pediatric Diabetes Visits - Louise Norman Jespersen; Jannet Svensson; Kasper Ascanius Pilgaard; Dan Grabowski (MDPI AG, 2022)
Clinical outpatient visits comprise a relatively small part of the lives of children with diabetes and their families, but there is evidence that these visits have a strong impact on the long-term management of diabetes. Because children with diabetes are looking at frequent hospital visits for the rest of their lives, it is important to explore their experiences to ensure visits meet their needs. This study aimed to investigate families' experiences with outpatient visits at a pediatric diabetes clinic. Thirteen semi-structured family interviews were conducted. Systematic text condensation was used to analyze the data. With an analytical focus on communication and social relations, nine themes were identified: 1. Discrepancies in perception of diabetes tasks, 2. Talking about adult things, but the children listen, 3. The importance of spoken and written words, 4. Confusion about division of responsibilities, 5. Relief when someone eases the burden, 6. Courtesy when visiting the clinic, 7. Understanding of the family context, 8. Importance of continuous personal relations, and 9. Need for a facilitated peer network. The findings encourage reflection on how to improve communication and underline the importance of establishing a continuous and personal relation between families and health care professionals to improve families' experience with pediatric outpatient visits.